Environmental and Behavioral Factors of “3M Plus” Practices (Cover, Drain and Recycle) Associated with Dengue Fever Incidence in Cilongok District, Banyumas Regency - Lailatul Mardhiyah; Suhartono Suhartono; Mursid Raharjo; Nur Endah Wahyuningsih; Sulistiyani Sulistiyani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Dengue hemorrhagic fever has been a public health concern in Cilongok District evident by a sharp increase in its cases in the last two years. This study aims to analyze the relationship between physical, biological, and social environmental factors, as well as the behavior of 3M Plus, with the incidence of dengue hemorrhagic fever in Cilongok District, Banyumas Regency. The research followed a quantitative approach of observational analytics with a case-control design. A total of 60 respondents were involved, consisting of 30 cases and 30 controls that were selected using neighborhood-matched controls based on a residential distance of less than 100 meters. Data analysis was carried out using chi square test and logistic regression. The results of the study show a cumulative increase in dengue cases from 26 cases in 2023 to 126 cases in 2024. Spatial analysis showed an uneven distribution of cases with high concentrations in densely populated areas, especially Langgongsari Village, Pageraji Village, and Panusupan Village. Indoor temperature was significantly associated with the incidence of dengue (p = 0.038; OR = 3.500), as well as air humidity (p = 0.039; OR = 3.455). Biological factors measured through the House Index (p = 0.398; OR = 1.902) and Container Index (p = 0.398; OR = 1.902) do not indicate a meaningful relationship. In social environmental factors, the habit of hanging clothes was significantly related to the incidence of dengue (p = 0.004; OR = 5.675), as well as the absence of gauze wire in house ventilation (p = 0.008; OR = 5,231). The other 3M Plus behavioral variables did not show a significant relationship. This study shows that the incidence of dengue fever in Cilongok District is influenced by microclimatic conditions in the house and specific behaviors that increase the chances of human-vector contact. Efforts to control dengue need to integrate ventilation and humidity management of the house with targeted behavior change interventions, especially reducing clothing storage in the room and increasing household physical protection Keyword: dengue hemorrhagic fever, environmental factors, 3M Plus behavior